Pengetahuan dan Sikap Mahasiswa Keperawatan terhadap Pemberian Asuhan Keperawatan Paliatif - Anggriyana Tri Widianti; Ita Nasilah; Inggriane Puspita Dewi; Nuni Apriani (Malahayati Nursing Journal, 2025)
ABSTRACT Death is one of the most intense emotional events experienced by anyone, including those in palliative conditions. There is an opinion that providing nursing care to patients who are at the end of life may be a challenge for nurses and nursing students, especially at their first encounter with a patient with palliative conditions. Students' knowledge and attitudes in handling palliative care are important to have. This study aims to identify the knowledge and attitudes of nursing students in managing palliative nursing care. The research method used is quantitative descriptive. The population of nursing students who carried out clinical learning practices using Proportionate stratified random sampling technique amounted to 61 respondents. The instrument used is the Frommelt Attitude Toward Care of Dying Patients Scale (FATCOD-C) to evaluate students' attitudes towards palliative care for patients and families and to evaluate knowledge of The Palliative Care Knowledge Questionnaire-Basic (PCKQ-B). The research results showed a sufficient level of knowledge (57.4%) and a positive attitude (50.8%). It is important for educational institutions to develop palliative nursing subjects in the core curriculum so as to facilitate students in managing palliative patients in clinical learning. Keywords: Attitude, Knowledge, Nursing Care, Palliative  Abstrak Kematian merupakan salah satu peristiwa emosional paling intens yang dialami siapa pun termasuk pada kondisi paliatif. Ada pendapat bahwa pemberian asuhan keperawatan pada pasien yang berada di akhir hayatnya mungkin bisa dilakukan tantangan bagi perawat dan mahasiswa keperawatan, terutama pada pertemuan pertama mereka dengan kondisi pasien dengan paliatif. Pengetahuan dan sikap mahasiswa dalam penanganan perawatan paliatif penting untuk dimiliki.  Mengidentifikasi pengetahuan dan sikap mahasiswa keperawatan dalam pengelolaan asuhan keperawatan paliatif. Metode penelitian yang digunakan adalah deskriftif kuantitatif. Populasi mahasiswa keperawatan yang melaksanakan praktik pembelajaran klinik dengan teknik sampel Proportionate stratified random sampling berjumlah sebanyak 61 responden. Instumen yang digunakan Frommelt Attitude Toward Care of Dying Patients Scale (FATCOD‐C) untuk mengevaluasi sikap mahasiswa dalam perawatan paliatif pada pasien dan keluarga dan untuk mengevaluasi pengetahuan The Palliative Care Knowledge Questionnaire-Basic (PCKQ-B). Penelitian menunjukan tingkat pengetahuan cukup (57.4%) dan sikap positif (50.8%). Cukupnya pengetahuan dan positifnya sikap terhadap perawatan paliatif, penting bagi institusi Pendidikan dalam mengembangkan mata ajar keperawatan palitif dalam kurikulum inti sehingga memfasilitasi mahasiswa dalam pengelolaan pasien paliatif pada pembelajaran klinik. Kata Kunci: Asuhan Keperawatan, Paliatif, Pengetahuan, Sikap